2020
DOI: 10.1155/2020/7152176
|View full text |Cite
|
Sign up to set email alerts
|

20(S)-Ginsenoside Rg3 Protects Kidney from Diabetic Kidney Disease via Renal Inflammation Depression in Diabetic Rats

Abstract: Rg3) has been shown to induce apoptosis by interfering with several signaling pathways. Furthermore, it has been reported to have anticancer and antidiabetic effects. In order to detect the protective effect of 20(S)-Rg3 on diabetic kidney disease (DKD), diabetic rat models which were established by administering high-sugar, high-fat diet combined with intraperitoneal injection of streptozotocin (STZ), and age-matched wild-type (WT) rat were given 20(S)-Rg3 for 12 weeks, with three groups: control group (norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Ginsenoside Rg3 suppresses tumour growth by enhancing apoptosis, decelerating proliferation, metastasis, and angiogenesis, increasing the chemosensitivity of tumour cells, and promoting host immunity [ 11 ]. As a multifunctional factor, Rg3 can also exert a protective effect on diabetic kidney disease by repressing the inflammatory response [ 30 ]. Additionally, Rg3 effectively ameliorated LPS-induced acute lung injury through certain specific pathways [ 14 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rg3 suppresses tumour growth by enhancing apoptosis, decelerating proliferation, metastasis, and angiogenesis, increasing the chemosensitivity of tumour cells, and promoting host immunity [ 11 ]. As a multifunctional factor, Rg3 can also exert a protective effect on diabetic kidney disease by repressing the inflammatory response [ 30 ]. Additionally, Rg3 effectively ameliorated LPS-induced acute lung injury through certain specific pathways [ 14 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB signaling cascade is the initial event in response to oxidative stress in diabetes ( Archuleta et al, 2009 ). A study showed that Rg3 decreased urine protein associated with DN in a rat model via inhibition of NF-κB p65 ( Zhou et al, 2020 ). Another study found that 20(S)-Rg3 ameliorated renal histopathological injury and dyslipidemia through the MAPK and NF-κB pathways in C57BL/6 mice with an intraperitoneal injection of STZ and a high-fat diet (HFD).…”
Section: Antioxidant and Anti-inflammatory Effects And Molecular Mech...mentioning
confidence: 99%
“…For diabetic complications, inhibition of the apoptotic signaling pathway can protect renal tissue in DN. Rg3 protected renal tubular epithelial cells from apoptosis in vitro ( Zhou et al, 2020 ). Li et al suggested that Rg3 reduced Bax and cleaved caspase3 and enhanced the expression of Bcl-2 and Bcl-XL to inhibit apoptosis in the kidneys of DN mice ( Li et al, 2021 ).…”
Section: Antioxidant and Anti-inflammatory Effects And Molecular Mech...mentioning
confidence: 99%
See 1 more Smart Citation
“…pathological changes of clinical DN patients are characterized by glomerular mesangial matrix expansion, glomerular basement membrane (GBM) thickening, and formation of glomerular nodular sclerosis [2][3] . The clinical manifestations of DN include hypertension, massive proteinuria, edema, and progressive decrease in renal function [4] . The precise mechanisms of DN pathogenesis are yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%